(untitled) (Malay Literature, 2019)
Abdullah Hussain’s novel, Interlok, has been the source of discussion and conflict among various factions in the multi-ethnic and multireligious community of Malaysia. As an alternative to some of the current negative impressions of the book, and accusations directed at the author, this essay presents a view of the novel and of the author’s motivations. It draws on two elements, evidences from the text itself, and an inward level or esoteric interpretation of the text. From an approach of Hindu religious and spiritual doctrines, and universal metaphysical truths from a Traditionalist perspective, it concludes that a fair and unbiased textual analysis which foregrounds Truth allows a genuine reader to understand what the author actually wrote, and to see beyond the conflict and accusations. Keywords: Hindu esoterism, discernment, Traditionalist perspective, human integration